Exploring the soft side of success: non-cognitive and social factors impacting attitudes towards adult education for GED students. Issue 5 (2nd November 2021) - Salusky, Ida R.; Reed, Jordan; Walker, Toni; Worthy, Glen; Gordon, Derrick
ABSTRACT: Adult education centres provide a final opportunity for adult learners who have transitioned out of mainstream schools to earn a high school degree. These centers overwhelmingly serve low-income, African-American and Latinx students whose needs were not met by traditional schools. Adult Education Centers are underfunded, under-resourced and challenged with high attrition rates. Little is known about factors that promote adult education persistence in the adult education context. To address this, the authors conducted a cross-sectional study examining the relationship between social support, coping through emotional processing and expression, stigma consciousness and attitudes towards participation in adult education. Results indicate that higher levels of self-reported coping (via emotional processing) and social support improve attitudes towards adult education and higher levels of self-reported stigma consciousness increase negative attitudes towards adult education. Study findings have significant policy implications for constructing student centred supports for adult education students who experience multiple levels of social inequality.